Analysis of Legal Culture and the Existence of Women in Village Head Election Contests in Sumenep Regency - Achmad Hariri; Holy Ichda Wahyuni (MUWAZAH : jurnal kajian gender, 2025)
This study aims to analyze the legal culture and the existence of women in grassroots democratic contestations in Sumenep Regency. Legal culture refers to the perceptions, attitudes, and behaviors of the community toward prevailing laws, which are often influenced by social, cultural, and historical factors. The existence of women in grassroots democratic contestations is crucial, as women play a vital role in social and political development at the local level.This research employs a qualitative approach, utilizing data collection techniques such as in-depth interviews, participatory observations, and document studies. The findings reveal that, despite growing awareness of the importance of women's participation in grassroots democracy, structural and cultural barriers still constrain their roles. Key obstacles include a strong patriarchal culture, limited access to education and information, and a lack of support from the social environment.Nonetheless, there are local initiatives striving to strengthen women's roles through various empowerment and legal education programs. Efforts to enhance women's participation in grassroots democracy in Sumenep Regency must adopt a holistic and sustainable approach, focusing not only on legal aspects but also on social and cultural transformation.Based on the research findings, it is recommended that local governments strengthen affirmative policies supporting women's involvement, expand access to political and legal education, and promote cross-sectoral collaboration in creating inclusive and gender-responsive participatory spaces. The active role of civil society organizations is also crucial in fostering legal culture change and enhancing women's leadership capacity at the local level.